2016
DOI: 10.1116/1.4944828
|View full text |Cite
|
Sign up to set email alerts
|

Waterborne chitosan–epoxysilane hybrid pretreatments for corrosion protection of zinc

Abstract: Biopolymer-based systems are extensively studied as green alternatives for traditional polymer coatings, e.g. in corrosion protection. Chitosan-epoxysilane hybrid films are presented in this work as a chitosan-based protective system, which could e.g. be applied in a pretreatment step. For the preparation of the chitosan-epoxysilane hybrid systems, a sol-gel procedure was applied. The function of the silane is to ensure adhesion to the substrate. On zinc substrates, homogeneous thin films with thickness of 50 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
20
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

4
4

Authors

Journals

citations
Cited by 9 publications
(22 citation statements)
references
References 61 publications
2
20
0
Order By: Relevance
“…A double logarithmic plot, in the style shown elsewhere, 8,12 confirmed that the progress of the delamination front scaled linearly with time t after an initiation phase where delamination progress scaled with an exponent > 1. (The fast initial delamination may be caused by the preparation method of the artificial defect used here.)…”
Section: Resultsmentioning
confidence: 78%
See 1 more Smart Citation
“…A double logarithmic plot, in the style shown elsewhere, 8,12 confirmed that the progress of the delamination front scaled linearly with time t after an initiation phase where delamination progress scaled with an exponent > 1. (The fast initial delamination may be caused by the preparation method of the artificial defect used here.)…”
Section: Resultsmentioning
confidence: 78%
“…7 (On the other hand, the presence of water and electrolytes is not sufficient for fast coating failure. 8 ) A further consequence is that the coating may start to delaminate, exposing more free metal surface. 9 The fastest mechanism of coating delamination initiated from a defect is cathodic delamination.…”
mentioning
confidence: 99%
“…47,48 For the measurements, the polymer-grafted samples were covered with a ≈1 μm thick, spin-coated PVB top layer to avoid electrolyte spreading above the PMMA modified surface. 4,49 Sample sets were assessed simultaneously in the SKP chamber, i.e. exposed to the same environment with the aim to avoid interference due to variations of oxygen partial pressure or relative humidity.…”
Section: Stability Of Polymer Layers-mentioning
confidence: 99%
“…Our group has recently investigated the possibility to use the biopolymer chitosan as ingredient in passive corrosion protection systems on zinc to limit ion mobility along the interface [11]. The cyclic oligosaccharide β-cyclodextrin was used to enhance corrosion inhibitor availability by incorporation into a model coating on zinc and into a zinc oxide based pretreatment [12,13].…”
Section: Introductionmentioning
confidence: 99%